Respuesta :

The formula is

[tex]x=\frac{-b+\sqrt{b^2-4ac}}{2a}[/tex]

and

[tex]x=\frac{-b-\sqrt{b^2-4ac}}{2a}[/tex]

This gives you 2 results :) Just insert your values
a= 2                b= -3          c= 1
firsly need to find discriminant.
D=b^2-4ac
                                                 (D= (-3)^2 - 4*2*1
                                                 D= 1)              
                                                  If  D>0, you get 2 
solutions.
Then
 formula is:

x1,2 =                  -b ± √D
                     _____________
                                  2 a
   

x1,2=              -(-3)+-(1)              = 3+-1            =  4    or     =  2
                     ____________         ______         ___              __
                            2*2                          4                 4                 4
ACCESS MORE